Synthesis and Anti-HIV Activity of Lupane and Olean-18-ene Derivatives. Absolute Configuration of 19,20-Epoxylupanes by VCD - Gutiérrez Nicolás, Fátima (2012)
Lupane triterpenoids 2 and 5–12 and oleanene derivatives 13 and 14 were prepared from lupeol (1), betulin (3), and germanicol (4). They were tested for anti-HIV activity, and some structure–activity relationships were outlined. The 20-(S) absolute configuration of epoxylupenone (8) was assessed by comparison of the observed and DFT-calculated vibrational circular dichroism spectra. The CompareVOA algorithm was employed to support the C-20 configuration assignment. The 20,29 double bond in lupenone (2) and 3-epilupeol (15) was stereoselectively epoxidized to produce 20-(S)-8 and 20-(S)-16, respectively, an assignment in agreement with their X-ray diffraction structures.